Changes in quaternary structure cause a kinetic asymmetry of glutamate racemase‐catalyzed homocysteic acid racemization. Issue 20 (24th September 2018) - Mackie, Joanna; Kumar, Himank; Bearne, Stephen L.
Abstract : Glutamate racemases (GR) catalyze the racemization ofd ‐ andl ‐glutamate and are targets for the development of antibiotics. We demonstrate that GR from the periodontal pathogen Fusobacterium nucleatum ( Fn GR) catalyzes the racemization ofd ‐homocysteic acid (d ‐HCA), whilel ‐HCA is a poor substrate. This enantioselectivity arises becausel ‐HCA perturbs Fn GR's monomer–dimer equilibrium toward inactive monomer. The inhibitory effect ofl ‐HCA may be overcome by increasing the total Fn GR concentration or by adding glutamate, but not by blocking access to the active site through site‐directed mutagenesis, suggesting thatl ‐HCA binds at an allosteric site. This phenomenon is also exhibited by GR from Bacillus subtilis, suggesting that enantiospecific, "substrate"‐induced dissociation of oligomers to form inactive monomers may furnish a new inhibition strategy. Abstract :